The impact of foreign direct investment on the economy of the people's republic of China : a macroeconomic model - Lim, Harold Chee Kian (2014)
This Applied Research Project (ARP) analyses foreign direct investment (FDI) in a macroeconomic framework. The econometric study is purely empirical in nature and thus throws new light on the various channels through which FDI influences five macroeconomic variables: economic growth, exports, imports, national saving and domestic investment. For the case of China, FDI appears to have a positive effect on economic growth, exports and imports, negative effect on national savings and no significant effect on domestic investment. Consequently, some policy prescriptions are derived from the results of this study.